2007
DOI: 10.1097/wnr.0b013e3282efa0a2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral activation patterns related to initiation and inhibition of hand movement

Abstract: Sequential ordering of purposeful movements includes distinct transitions between muscle contraction and relaxation. To explore cerebral activation patterns underlying such movement initiation and inhibition, we applied functional magnetic resonance imaging to test the effects of (1) ballistic movement (dominated by initiation), (2) movement with stepwise interruption (dominated by inhibition) and (3) smooth movements. Right-hand movements were performed by 21 healthy participants. In the basal ganglia, ballis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…Since the putamen is also involved in initiating hand movement (62), a pairwise comparison of the two patient groups was conducted using an ANCOVA with frequency and duration of button-pressing during scanning plus negative symptoms considered as covariates. Corticostriatal FC for hallucinators remained robustly greater than for nonhallucinating patients after these adjustments ( F (1,51)=18.9, p =0.00007).…”
Section: Resultsmentioning
confidence: 99%
“…Since the putamen is also involved in initiating hand movement (62), a pairwise comparison of the two patient groups was conducted using an ANCOVA with frequency and duration of button-pressing during scanning plus negative symptoms considered as covariates. Corticostriatal FC for hallucinators remained robustly greater than for nonhallucinating patients after these adjustments ( F (1,51)=18.9, p =0.00007).…”
Section: Resultsmentioning
confidence: 99%
“…Both Clear conditions engaged the SMA, which has been associated with the inhibition or cessation of movement (e.g., Dinomais et al 2009; Milham & Banich, 2005; Toxopeus et al 2007), and may be associated with the “cessation” of retaining an item in WM or within the focus of attention. In contrast, the Global Clear condition yielded activation more ventrally in the vicinity of and below the cingulate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Kraft et al (2007) reported enhanced BG activity when initiating anti-phase hand movements but did not show any difference in putamen activity between mirror and parallel patterns during continuous execution, a finding in keeping with the present result that striatum is involved in selecting and switching between patterns in a stability-dependent manner but not in pattern execution per se. Furthermore, Toxopeus et al (2007) showed BG and SMA activity in response to both movement initiation and inhibition, and Li et al (2008) detected putamen activity correlated with oscillation frequency in a study on motor response inhibition during a stop signal task. Yehene et al (2008) further reported deficits in task switching in patients with focal lesions within frontal-subcortical circuits.…”
Section: Discussionmentioning
confidence: 99%